Self-regulated pacing in biathlon: how shooting impacts skiing strategy compared to cross-country skiing - Losnegard, T.; Stubbe, E. V.; Sakalidis, K. E.; Lund-Hansen, M.; Kocbach, J.; Hettinga, F. (Sport Sciences for Health, 2026)
Purpose Biathlon, a unique combination of cross-country skiing and precision rifle shooting, offers an intriguing subject for the study of pacing behavior. We examined the impact of shooting on pacing behavior in highly trained biathletes.